Dinamika aktivitas penangkapan ikan dan pendapatan nelayan disekitar kegiatan pertambangan Desa Batuawu Kecamatan Kabaena Selatan Kabupaten Bombana - Sidiq, Azwar; Arsal, La Ode Muhammad; Risfandi (Jurnal Sosial Ekonomi Perikanan, 2023)
Mining activities have caused damage to ecosystems in coastal areas and disruption of fishing activities. This study aims to determine the dynamics of fishing activities, income levels, and adaptation strategies of Batuawu Village fishermen due to mining activities. Respondents were taken using the census method, as many as 18 Fishing Households (RTP). The data were analyzed using quantitative descriptive analysis. The results showed that fishing activities were generally carried out by "one day fishing". In the peak season, the average fishing trip is 15 days/month, while in the lean season it is 5 to 10 trips/month. The average boat size is smaller than 2 GT, equipped with engines between 5.5 PK and 16 PK. Mining activities have caused turbidity and decreased water quality, which has contributed to a decrease in fishermen's catches. The farthest fishing grounds are around the South Buton border of "Kokoe", and the closest around Sagori Island. Most fishers accessing the more distant fishing grounds use bottom longlines and arrows to catch demersal fish with high economic value. The presence of mining activities also affects the increase in demand for consumable fish, especially for company needs, so that fish prices become more expensive. On the other hand, these conditions have a negative impact on local communities, especially low-income communities. The income of fishermen in Batuawu Village is Rp3,380,307 per month or still above the Bombana Regency Minimum Wage (UMK). Adaptation strategies carried out by fishermen in order to deal with the decline in coastal environmental conditions are to change fishing gear and fishing locations, to catch demersal fish that have higher economic value.